2014 IEEE Symposium on Computational Intelligence and Data Mining (CIDM) 2014
DOI: 10.1109/cidm.2014.7008682
|View full text |Cite
|
Sign up to set email alerts
|

Patient level analytics using self-organising maps: A case study on Type-1 Diabetes self-care survey responses

Abstract: Diabetes is considered a lifestyle disease and a well managed self-care plays an important role in the treatment. Clinicians often conduct surveys to understand the self-care behaviours in their patients. In this context, we propose to use Self-Organising Maps (SOM) to explore the survey data for assessing the self-care behaviours in Type-1 diabetic patients. Specifically, SOM is used to visualise high dimensional similar patient profiles, which is rarely discussed. Experiments demonstrate that our findings th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A dimensional reduction in heterogeneous diabetes dataset using Self Organizing Map (SOM) clustering was performed and established similarities among patients using (Unified distance) U-Matrix [ 6 ]. Questionnaires consisting of both text as well as numeric responses were used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A dimensional reduction in heterogeneous diabetes dataset using Self Organizing Map (SOM) clustering was performed and established similarities among patients using (Unified distance) U-Matrix [ 6 ]. Questionnaires consisting of both text as well as numeric responses were used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SOM is used an un-supervised learning framework to cluster the profiles He used 7×12 hexagonal grid mapping with Gaussian neighborhood functions to detect the similarities and variations in the variables. In another research, conducted by author [2] have used the techniques of SOM to study the behavior of type 1 diabetic patients. From his research outcomes, there were suggestions provided to change or adjust the life style to control diabetics.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, SOMs have been used to visually explore financial [2], gene expression [3], linguistics [4] and medical survey [5] datasets. Toronen et al [6] used SOMs to analyse yeast gene expression data, and demonstrated its suitability for analysing and visualising gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that SOMs can be used to identify co-morbidities, link self-care factors that are dependent on each other and to visualise individual patient profiles in clinically useful ways, e.g. by giving a visual summary of individual patient profiles and enabling patients to be grouped together [5]. SOMs are therefore a potentially valuable tool for visually analysing high-dimensional medical questionnaire responses, as well as a means to visually summarise an individual patient's data.…”
Section: Introductionmentioning
confidence: 99%